Epithelial to mesenchymal transition in human endocrine islet cells. - José Luis Moreno-Amador; Noèlia Téllez; Sandra Marin; Caterina Aloy-Reverté; Carlos Semino; Montserrat Nacher; Eduard Montanya (PLoS ONE, 2018)
β-cells undergo an epithelial to mesenchymal transition (EMT) when expanded in monolayer culture and give rise to highly proliferative mesenchymal cells that retain the potential to re-differentiate into insulin-producing cells.To investigate whether EMT takes place in the endocrine non-β cells of human islets.Human islets isolated from 12 multiorgan donors were dissociated into single cells, purified by magnetic cell sorting, and cultured in monolayer.Co-expression of insulin and the mesenchymal marker vimentin was identified within the first passage (p1) and increased subsequently (insulin+vimentin+ 7.2±6% at p1; 43±15% at p4). The endocrine non-β-cells did also co-express vimentin (glucagon+vimentin+ 59±1.5% and 93±6%, somatostatin+vimentin+ 16±9.4% and 90±10% at p1 and p4 respectively; PP+vimentin+ 74±14% at p1; 88±12% at p2). The percentage of cells expressing only endocrine markers was progressively reduced (0.6±0.2% insulin+, 0.2±0.1% glucagon+, and 0.3±0.2% somatostatin+ cells at p4, and 0.7±0.3% PP+ cells at p2. Changes in gene expression were also indicated of EMT, with reduced expression of endocrine markers and the epithelial marker CDH-1 (p<0.01), and increased expression of mesenchymal markers (CDH-2, SNAI2, ZEB1, ZEB2, VIM, NT5E and ACTA2; p<0.05). Treatment with the EMT inhibitor A83-01 significantly reduced the percentage of co-expressing cells and preserved the expression of endocrine markers.In adult human islets, all four endocrine islet cell types undergo EMT when islet cells are expanded in monolayer conditions. The presence of EMT in all islet endocrine cells could be relevant to design of strategies aiming to re-differentiate the expanded islet cells towards a β-cell phenotype.